Krisis Identitas di Era Media Sosial: Tinjauan atas Pemikiran Agustinus dari Hippo - Yohakim Polohae Ritan; Mario Antonius Wato Tukan (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
The phenomenon of identity crisis in the era of social media has become an increasing evident existential problem in contemporary human life. Individuals tend to construct their identities based on external recognition, such as social validation, popularity, and digital representations that are often unstable. This article aims to examine this identity crisis trough a medieval perspective, particularly the thought of Agustine of Hippo. Using a qualitative method, this study explores the concept of inquietum cor (the restless heart) and the idea of human beings as creatures who find their fulfillment only in relation to God. The findings show that the identity crisis in the social media era can be understood as a form of human alienation from the true source of meaning. When identity is built upon temporal and external elements, individuals experience restslessness, dissatisfaction, and a loss of life direction. Agustine’s thought offers a reflective framework in which true identity is transcendent and rooted in a relationship with God as the highest good (summum bonum). Thus, Agustine’s philosophy remains relevant as a critique of the shallow construction of modern identity, as well as a proposed solution for building a more authentic and meaningful identity amid the currents of digitalization.